2016
DOI: 10.7751/telopea10722
|View full text |Cite
|
Sign up to set email alerts
|

Free Axial Lobes: An Important Diagnostic Character in Pteridium (Dennstaedtiaceae)

Abstract: The overall form of the lamina in the bracken fern (Pteridium) is a fractal series in which blade, pinnae, pinnules and pinnulets represent a hierarchy of repeated units of decreasing size. Distinctive lunate or semilunate lobes of laminal tissue between the divisions of the blade in an apical zone of some or all of its axes are an important diagnostic feature. These "free lobes" link Pteridium esculentum (G. Forst.) Cockayne subsp. esculentum from Australasia with P. esculentum subsp. arachnoideum (Kaulf.) J.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…For example, in P. aquilinum , a species widely distributed in the Northern Hemisphere from North America and across Eurasia and sub‐Saharan Africa, Der et al (2009) and Wolf et al (2019) both found molecular support for most distinct morphological subspecies (Thomson et al, 2005, 2008), which at the same time corresponded with geographic location. A similar pattern could be expected for Southern Hemisphere P. esculentum at the subspecific level (Thomson, 2016), but our findings in the present study suggest that the story may be more complicated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example, in P. aquilinum , a species widely distributed in the Northern Hemisphere from North America and across Eurasia and sub‐Saharan Africa, Der et al (2009) and Wolf et al (2019) both found molecular support for most distinct morphological subspecies (Thomson et al, 2005, 2008), which at the same time corresponded with geographic location. A similar pattern could be expected for Southern Hemisphere P. esculentum at the subspecific level (Thomson, 2016), but our findings in the present study suggest that the story may be more complicated.…”
Section: Discussionsupporting
confidence: 90%
“…Thomson (2016) suggested that the observed morphological variability within Pteridium is likely related to genetic polymorphisms. Wolf et al (2019) found population structure correlating to the subspecies of P. aquilinum , but detected no population structure within South American and Australian populations of P. esculentum .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Pteridium (bracken fern) is a fern genus distributed world-wide. The circumscription of species is widely discussed in the literature, about 20 morphotypes have been recognized, and several infra-specific ranks have been adopted (PPG I 2016, Thomson 2016. While some authors recognize only two species: Pteridium aquilinum (L.) Kuhn and P. esculentum (G.…”
Section: Introductionmentioning
confidence: 99%
“…Forst.) Cockayne along their infraspecies (Thomson 2016). All the species of the genus have nectaries on their fronds (fern leaves) (Tryon & Tryon 1982), and the oldest record of nectaries in ferns was reported by Francis Darwin in 1877 for Pteridium aquilinum (L.) Kuhn (Lloyd 1901).…”
Section: Introductionmentioning
confidence: 99%